Scars of early non-employment for low educated youth: Evidence and policy lessons from Belgium - Corinna Ghirelli (IZA Journal of European Labor Studies, 2015)
This paper investigates whether the early experience of non-employment has a causal impact on workers' subsequent career. The analysis is based on a sample of low educated youth graduating between 1994 and 2002 in Flanders (Belgium). To correct for selective incidence of non-employment, we instrument early non-employment by the provincial unemployment rate at graduation. Since the instrument is clustered at the province-graduation year level and the number of clusters is small, inference is based on wild bootstrap methods. We find that one percentage point increase in the proportion of time spent in non-employment during the first two and a half years of the career decreases annual earnings from salaried employment six years after graduation by 10% and annual hours worked by 7% (unconditional effects). Thus, any policy that prevents unemployment in the first place will be beneficial. In addition, curative policies at the micro level may be required, depending on the actual cause of the scar.
Keywords: J31; J64; 330; Youth unemployment; Scars; Instrumental variable; Wild bootstrap